Vertical electrical sounding method and Dar Zarrouk analysis to identify the distribution of seawater intrusion in Pelauw Village, Maluku - Bahri, Samsul; Tualepe, Daramahu; Batlolona, Yohanis Toni; Ramadhan, Aditya; Parnadi, Wahyudi Widyatmoko (Journal of Degraded and Mining Lands Management, 2024)
Groundwater is one of the essential resources that support human life. Excessive exploitation activities can cause groundwater problems such as seawater intrusion, especially in coastal areas. Groundwater salination must be a concern and measured to determine the condition and level of distribution. One of the non-invasive, inexpensive, and efficient methods to see seawater intrusion phenomena is the vertical electrical sounding (VES) technique of electrical resistivity method. This research aimed to analyze the distribution of seawater intrusion in Pelauw Village, Maluku, Indonesia, using the VES and Dar-Zarrouk parameters S and T. The S and T are longitudinal conductance and transversal resistance, respectively. This study collected 16 VES stations spread across residential areas near the coast of Pelauw Village. Groundwater affected by seawater intrusion in the study area has S>1.00 mho and T<1,000 ohm m2. Three VES stations are suspected to have experienced seawater intrusion, namely V7, V8 and V12. These three stations are located near the shoreline and densely populated areas. Based on the 2D cross-section, the spread of seawater intrusion toward the land is about 200 meters. This seawater intrusion event is thought to have occurred due to groundwater exploitation by communities around the coast and active tectonic activity. The VES method and Dar Zarrouk Analysis proved compelling enough to delineate the spread of seawater intrusion, so based on these results, it can be a reference for mitigating groundwater pollution.